The Diversity Of Fish Species In Inland Water Of Kampung (Village) Nasem In Merauke District - Norce Mote; Rosa Delima Pengaribuan (Musamus Fisheries and Marine Journal, 2021)
Wetland or stagnant swamp refers to an ecosystem of inland water that is vulnerable to population decline. Kampung Nasem in Merauke has quite promising fish resources. This research aimed to determine the diversity of fish species found in Kampung Nasem of Merauke. The fish sampling was performed for three months, from September to November 2017 at three research stations by functioning digital camera, ruler and manual as tools for documentation, while tool for fishing used gill net in the size of 1, 1.5, 2, 2.5, 3 and 4 inches; casting nets and scoop net. Fish found in the field were preserved with 10% formalin for identification purpose in the laboratory. The observed biological parameters were species richness, diversity index (H’), evenness index (E) and dominance index (C). The research finding obtained 15 fish species richness coprising 11 native fish species and 5 introduced fish species. The value of H’ was classified into moderate while the uniformity value was high, hence the fish were spread evenly in each research site and no species was found with domination. In addition, the Tilapia (Oreochromis niloticus) and Glass (Agrammus ambassadors) were species to have sufficient widespread distribution and numerous presence of presentation within the three research stations.